The Effectiveness of Pontianak’s Chili Orange Juice as an Alternative Dentin Conditioner - Jojok Heru Susatyo; Rusmali Rusmali; Pawarti Pawarti (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
Abstract The use of dentin conditioner is needed on the Glass Ionomer lift so that the surface of the dentin is clean and the glass ionomer cement lift material can well adhere to the clean dentin surface. In its use in the field, the dentin conditioner used is 10% polyacrylic acid or using liquid from diluted Glass Ionomer Cement, this causes the available liquid to run out compared to the powder provided, therefore it is thought to look for alternative materials as a dentin conditioner. The purpose of this study was to determine the effectiveness of Pontianak chili orange juice on the cleanliness of the smear layer on the tooth surface and the tensile strength of the glass ionomer cement lift after preparation and polishing of the tooth surface.This type of research is an experimental laboratory, the sample used a number of 5 samples per treatment for dentin surface cleanliness and 7 samples per treatment for the tensile strength test. The results obtained were analyzed using a t-test.The results showed that the average surface hygiene of dentin using Pontianak chili orange was 2 while the control mean was 2.2, while the Tensile strength with Pontianak chili orange treatment, it was obtained 1.8 meanwhile the mean control was 3.18.The conclusion of this study is that the use of Pontianak chili oranges is effective for cleaning dentin surfaces but not effective for increased tensile strength.